REALITAS KEMANUSIAAN DALAM RUBRIK SOSOK HARIAN KOMPAS (ANALISIS WACANA TEUN A. VAN DIJK) (Fakultas Dakwah dan Komunikasi, 2020)
The purpose of this study was to determine the reality of humanity that was presented by Kompas Daily in the rubric of the Figure. This study used a qualitative type with a text discourse analysis model of the Teun A. van Dijk model. The subjects of this study were three feature profile posts in the rubric of Figure, each entitled